2021
DOI: 10.1007/s00005-021-00620-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in γδT Cells in Peripheral Blood of Patients with Ulcerative Colitis Exacerbations

Abstract: The role of γδT cells in ulcerative colitis (UC) is well confirmed in experimental animals and demonstrated in many clinical observations. Recent investigations have indicated that UC is associated with several forms of immune imbalance, such as an imbalance between effector T cells and regulatory T cells. However, little is known about the cellular aspect of clinical colitis exacerbations. We observed 140 patients with histologically confirmed UC over the course of 8 years. We investigated the percentage of γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…39 However, a lot of adverse events caused by those drugs have also been recorded. 13 Other newly developed specific antibodies such as infliximab, adalimumab, and CD54 antagonist ISIS 2302 have an excellent therapeutic effect on UC with fewer side effects, [40][41][42] but the high prices have limited their wide application in clinical treatment. Thus, it is of profound significance to find drugs with few adverse reactions and low cost.…”
Section: Discussionmentioning
confidence: 99%
“…39 However, a lot of adverse events caused by those drugs have also been recorded. 13 Other newly developed specific antibodies such as infliximab, adalimumab, and CD54 antagonist ISIS 2302 have an excellent therapeutic effect on UC with fewer side effects, [40][41][42] but the high prices have limited their wide application in clinical treatment. Thus, it is of profound significance to find drugs with few adverse reactions and low cost.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with colonoscopy, these detection methods taking advantage of such indicators are more convenient, and patients are more likely to agree to undergoing these analyses. Gryglewski et al [ 10 ] found that patients with progressive UC have reduced γδ T cells in the peripheral blood, increased αβ/γδ T-cell ratios, and significantly increased percentages of γδTCD25, γδTCD54, and γδTCD62L lymphocytes compared with patients with stable UC. These observations might provide markers for predicting exacerbations in UC patients.…”
Section: Introductionmentioning
confidence: 99%